Registration of Arkot 0611, Arkot 0617, and Arkot 0712 Cotton Germplasm Lines. Issue 1 (4th October 2018) - Bourland, Fred M.; Cook, Charles; Jones, Don C.
Abstract : Arkot 0611 (Reg. No. GP‐1035, PI 687864), Arkot 0617 (Reg. No. GP‐1037, PI 687866), and Arkot 0712 (Reg. No. GP‐1036, PI 687865) are conventional germplasm lines of cotton ( Gossypium hirsutum L.) released by the Arkansas Agricultural Experiment Station (AAES) in April 2018. The lines were released as part of an ongoing effort to develop improved genotypes with enhanced yield, yield components, earliness, host plant resistance, and fiber properties. They share one common parent, DX25105N, a privately developed line made available to AAES by a Memorandum of Agreement. All three lines produced equal or higher lint yields than 'DP 393' and 'UA48' over 4 yr and at four test sites in Arkansas. Over all test sites, Arkot 0611 produced 10 and 22% higher lint yields than DP 393 and UA48, respectively. Both Arkot 0617 and Arkot 0712 produced 12% more lint than UA48. Lint percentage, seed per hectare, fibers per seed, and fiber density of each line were greater than UA48 and equal to or greater than DP 393. Compared with the check cultivars, all three lines were earlier maturing, but Arkot 0611 and Arkot 0617 tended to have taller plants. All three lines produced more dense leaf pubescence and bract trichomes than either check cultivar. Fiber quality of Arkot 0611 was inferior to either check, and fiber quality of Arkot 0617 and Arkot 0712 was higher than DP 393 but lower than UA48. The DX250105N parent of these lines increases the genetic diversity with the AAES cotton breeding program and broadens the available cotton germplasm pool.